ANALISIS YURIDIS SENGKETA TERHADAP PENDAFTARAN MEREK YANG MENGGUNAKAN SIMBOL LIMA RING OLIMPIADE ANTARA KOI DAN KONI (PUTUSAN PENGADILAN NIAGA NO. 68/PDT.SUS/MEREK/2-14/PN/JKT/PST) - MUHAMMAD ARIF PRASETYO (PREMISE LAW JURNAL, 2017)
A brand is a sign or a group of signs which can distinguish goods and services of one company from the other companies. For the recognition of a certain brand, the owner of the brand has to register it to the Directorate General of HAKI. In the verdict in the Commerce Court No 68/Pdt.Sus.Merek/2014/PN/Jkt.Pst, there a case of dispute in brand registration in which KOI and KONI compete over the Logo of Olympics Five Rings. The research problems include the existence of Logo of Olympics Five Ring in Indonesia, the evidence of the dispute in brand registration between KOI and KONI in the Commercial Court No. 68/Pdt.Sus.Merek/2014/PN/Jkt.Pst, and judge’s legal consideration in the Verdict No 68/Pdt.Sus.Merek/2014/PN/Jkt.Pst.